1991
DOI: 10.1097/00000658-199107000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Acute Appendicitis Following Blunt Abdominal Trauma

Abstract: Inflammation of the appendix is a common cause of acute abdominal pain. The etiology and pathophysiology of appendicitis have been well described. The initiating factor often is obstruction of the appendiceal lumen by inspissated stool, barium, food, parasites, or hyperplastic lymphoid tissue. Two patients have been identified who developed appendicitis temporally related to blunt abdominal trauma, without other clear etiology. Although absolute documentation of trauma as an etiologic factor in these cases is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 3 publications
0
30
0
Order By: Relevance
“…Because of the frequency of both events and the propensity for both conditions to occur in children and young adults, some authors have attributed acute appendicitis in the injured to coincidence. 3 Others have proposed various theories to explain their co-existence ( The present case is convincing of a cause and effect relationship. There was direct trauma to the right flank and lower quadrant.…”
Section: Discussionmentioning
confidence: 51%
“…Because of the frequency of both events and the propensity for both conditions to occur in children and young adults, some authors have attributed acute appendicitis in the injured to coincidence. 3 Others have proposed various theories to explain their co-existence ( The present case is convincing of a cause and effect relationship. There was direct trauma to the right flank and lower quadrant.…”
Section: Discussionmentioning
confidence: 51%
“…Hennington et al in their report on one adult and one paediatric patient noted that following BAT with a direct effect on the appendix, appendiceal oedema, inflammation, and/or hyperplasia of intrinsic lymphoid tissues had resulted in obstruction of the appendiceal lumen. 3 Çiftçi et al reported a series of five children with TA following direct trauma, suggesting the same mechanism. 2 Oedema and haematoma of the caecal wall and the root of the appendix, revealing possible direct trauma to the appendix, was identified in our case 2 but he also had associated intra-abdominal injuries.…”
Section: Discussionmentioning
confidence: 91%
“…reported two cases of blunt abdominal trauma producing acute appendicitis. In both cases, blunt abdominal trauma has produced appendiceal edema with inflammation and hyperplasia of appendix lymphoid tissue, and then, obstruction of the appendiceal lumen, leading to acute appendicitis [4]. Ciftçi and al reported 5 cases of appendicitis occurring after abdominal trauma suggesting the same mechanism [2].…”
Section: Discussion:-mentioning
confidence: 99%